2015
DOI: 10.1186/s13395-014-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

X-linked myotubular myopathy in Rottweiler dogs is caused by a missense mutation in Exon 11 of the MTM1 gene

Abstract: BackgroundCongenital and inherited myopathies in dogs are faithful models of human muscle diseases and are being recognized with increasing frequency. In fact, canine models of dystrophin deficient muscular dystrophy and X-linked myotubular myopathy are of tremendous value in the translation of new and promising therapies for the treatment of these diseases. We have recently identified a family of Australian Rottweilers in which male puppies were clinically affected with severe muscle weakness and atrophy that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 41 publications
2
65
0
Order By: Relevance
“…Sporadic fusion of SCs into myofibers occurs in resting skeletal muscles, with or without cell cycle entry5354. Consistently, we observed both EdU + MyoG + and EdU − MyoG + cells in resting muscles of WT mice.…”
Section: Discussionsupporting
confidence: 85%
“…Sporadic fusion of SCs into myofibers occurs in resting skeletal muscles, with or without cell cycle entry5354. Consistently, we observed both EdU + MyoG + and EdU − MyoG + cells in resting muscles of WT mice.…”
Section: Discussionsupporting
confidence: 85%
“…A variety of progressive neurologic diseases occur in young Rottweilers and are presumed to be hereditary (Table ) . The clinical histories of the RAB3GAP1:c.743delC homozygotes in the current study most closely resemble those previously reported for dogs with NVSD.…”
Section: Discussionsupporting
confidence: 77%
“…A number of presumed hereditary neurologic diseases occur in young Rottweiler dogs . As discussed in reviews of these diseases, there is considerable overlap in clinical signs and ages of onset which can make antemortem differentiation of the conditions difficult.…”
mentioning
confidence: 99%
“…Yet, limitations remain for the use of AONs, including variable efficiencies of tissue uptake, depending on AON chemistry, a requirement for repeated AON injection to maintain effective skipping, and the potential for AON-associated toxicities ((9, 10) and Supplementary Text). …”
mentioning
confidence: 99%